Ancestral Characteristics of Modern Populations. Issue 1 (2nd January 2018) - Giuliano, Paola; Nunn, Nathan
ABSTRACT: We construct a database, with global coverage, that provides measures of the cultural and environmental characteristics of the pre-industrial ancestors of the world's current populations. In this paper, we describe the construction of the database, including the underlying data, the procedure to produce the estimates, and the structure of the final data. We then provide illustrations of some of the variation in the data and provide an illustration of how the data can be used.